Correlation between Preoperative Hearing Evaluation with Intra-operative Ossicular Status in COM Mucosal - Tripathi, Prashant (Nepalese Journal of ENT Head and Neck Surgery, 2018)
Objective: To correlate the preoperative pure tone audiogram findings with intra-operative status of ossicular chain in patients with chronic otitis media mucosal type. Material and Methods: Prospective, descriptive study conducted over a period of twenty months at GMSMA of ENT-Head and Neck Studies, TUTH, IOM, Kathmandu, Nepal. Patients included in the study were both children and adults with central perforation in tympanic membrane which was dry for at least 4 weeks. Patients with SNHL or mixed HL and in those where ossicular status was not assessed were excluded from study. Results: There were 274 patients operated for COM Mucosal and 67 patients were excluded from study as they did not meet inclusion criteria. Hence, there were 207 patients included in the study. Out of them, 4 (1.9%) patients had minimal hearing loss, 73 (35.3%) had mild hearing loss, 117 (56.5%) had moderate hearing loss and 13 (6.3%) had severe hearing loss. On correlating with ossicular status, when there was discontinuity of ossicular chain average hearing loss was more than 50 dB and none of the patients had mild hearing loss. When there were restricted or fixed ossicles, there was moderate to severe hearing loss in majority of cases (85%). With intact and mobile ossicles, about 95% patients had mild to moderate hearing loss. When there was only mild hearing loss, 90% patients had intact and mobile ossicles and 10% had ossicular fixation or restricted mobility. Conclusion: In our study, we found that preoperative pure tone audiogram can predict the possibility of the involvement of the ossicular chain in patients with COM Mucosal. Ossicular involvement is more common with moderate to severe hearing loss either in the form of fixation or discontinuity. Nepalese Journal of ENT Head and Neck Surgery, Vol. 5, No. 2, 2014, Page: 15-17